Motivation to study as a pedagogical condition for the formation of cross-cultural competence of future agrarian economists (Pedagogy of Higher and Secondary Education, 2012)
Rezunov A. S. Motivation to study as a pedagogical condition for the formation of cross-cultural competence of future agrarian economists.It is shown the importance motivation for cross-cultural competence formation in a process of agrarian students education at economic faculties.
Keywords: motivation; internal motivation; external motivation